(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
In Lithuania, over the recent years a highly-skilled heptathlon athlete has been developed. She made her international debut in the Sidney Olympic Games in 2000 and took the 12 th place. Every year she kept improving her skills and excellently prepared for the XXVIII Olympic Games in Athens where she won a silver medal. Track-and-field heptathlon requires excellent physical fitness, development of all specific features, as well as good physical fitness for each contest. While planning the process of a heptathlon athlete’s training, it is most important to elaborate an optimum structure of an annual cycle with regard to the competition schedule and the individual potential of human adaptation. To be able to control the process, it is necessary to monitor the dynamics of the physical and functional abilities of the athlete in different periods of the annual cycle of training. The aim of the study was to analyse the dynamics of sports results of the Lithuanian heptathlon athlete A. S. in a four- year Olympic cycle and the dynamics of her physical and functional abilities over this period. We analyzed the dynamics of the sports results of A. S. over the last five years. Her body composition indices were measured in laboratory, with determining psychomotor response time and movement frequency per 10 s. To determine her physical abilities, we measured her single muscular contraction power (SMCP), anerobic alactic muscular power (AAMP). A running-track was used to establish the intensity of energetic processes at the anaerobic threshold level, with measuring heart rate (HR), running speed (km / h) and blood lactate concentration. The functional capacity of the circulatory and respiratory systems was assessed by the Roufier index (RI). Anaerobic capacity was measured with a gas analyzer at the critical intensity and anaerobic metabolism limits. The sports results of A. S. kept improving every year except 2003. In the 2004 Olympic Games she gathered 6435 points and won the second place. In previous years, in separate heptathlon contests the sum total of her points reached 12.7— 15.6%, whereas in the 2004 Olympic Games the difference among scores got in separate contests was less. Most points were won in the 100-m hurdling (15.1%) and the least in javelin throwing (13.3%). Data of laboratory tests showed that the quality of the SMCP and AAMP indices, which are decisive in even five contests of heptathlon, over the four-year Olympic cycle showed a waved dynamics, but attained a high level one month before the Olympic start: her SMCP was 3.22 kgm / s / kg and AAMP 1.72 kgm / s / kg. Also, greatly improved her psychomotor response time, which reached 160 mls, and central nervous system lability (78 movements per 10 s). Her high muscular power was confirmed by performing ten jumps on a running-jumping track, when the difference between the highest and lowest jumps was insignificant and muscular fatigue in a series of jumps was low. In the final period of the preparation for the Olympic Games under a short-lasting load the muscular power of A. S. reached a high level and allowed her to realize physical and functional abilities. Keywords: heptathlon, four-year Olympic cycle, physical abilities, functional capacity, physical and functional abilities.